2021
DOI: 10.1073/pnas.2017749118
|View full text |Cite
|
Sign up to set email alerts
|

Orthosteric–allosteric dual inhibitors of PfHT1 as selective antimalarial agents

Abstract: Artemisinin-resistant malaria parasites have emerged and have been spreading, posing a significant public health challenge. Antimalarial drugs with novel mechanisms of action are therefore urgently needed. In this report, we exploit a “selective starvation” strategy by inhibiting Plasmodium falciparum hexose transporter 1 (PfHT1), the sole hexose transporter in P. falciparum, over human glucose transporter 1 (hGLUT1), providing an alternative approach to fight against multidrug-resistant malaria parasites. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…In the course of investigating various families of transport proteins we first isolated, functionally characterised in Xenopus oocytes, and genetically validated the parasite's hexose transporter, PfHT, as a new drug target 37 . Co-crystallisation of PfHT with the selective inhibitor we characterised has confirmed that structure-based design of inhibitors against integral membrane proteins of P. falciparum is feasible 38 .…”
Section: Discussionmentioning
confidence: 69%
“…In the course of investigating various families of transport proteins we first isolated, functionally characterised in Xenopus oocytes, and genetically validated the parasite's hexose transporter, PfHT, as a new drug target 37 . Co-crystallisation of PfHT with the selective inhibitor we characterised has confirmed that structure-based design of inhibitors against integral membrane proteins of P. falciparum is feasible 38 .…”
Section: Discussionmentioning
confidence: 69%
“…As an essential component of the glucose–lactate transport cycle, PfFNT, together with PfHT1, is vital for the energy supply and metabolic homeostasis of parasites [ 9 , 10 ]. The energy supply of parasites can be cut off by inhibiting glucose uptake, making PfHT1 a valuable drug target for next-generation antimalarial development [ 12 14 ]. PfFNT, hence, represents another Achilles’ heel of this transport cycle that can be exploited for chemotherapeutic development of malaria.…”
Section: Introductionmentioning
confidence: 99%
“…D-glucose is taken up via the erythrocyte's glucose transporter, GLUT1 [8,9], and the parasite's hexose transporter, HT [10,11]. The protein structures of the human [12,13] and recently of the plasmodial glucose transporters [14] have been resolved at high resolution. Such transporters are themselves attractive targets for the design of antimalarials [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Such transporters are themselves attractive targets for the design of antimalarials [15][16][17]. In fact, the HT structure and a human homolog, GLUT3, were elucidated in the presence of an inhibitor, C3361, and the structures were used successfully to optimize the affinity of the small molecule [13,14]. Such compounds exhibit antimalarial activity in parasite cultures by blocking glycolysis via HT-inhibition [13][14][15]17] or by inducing apoptosis via redox stress when acting on the erythrocyte GLUT [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation